Fenomena LGBT dalam Perspektif HAM dan Doktrin Agama (Solusi dan Pencegahan) - Abdul Malik Ghozali (Faculty of Ushuluddin Syarif Hidayatullah State Islamic University, 2017)
Lesbian, Gay, Bisexual and Transgender movements are now a mondial phenomenon. The LGBT community has dared to show itself to the surface. Not only in the Western world alone, but LGBT excitement also rife in the homeland. The emergence of LGBT community in the midst of people's life raises pro and contra. Some people criticize the existence of the LGBT community, because it is considered a people with abnormal behavior and deviates from religious teachings. Others accept it as part of appreciating their exclusion in Human Rights. This study attempts to answer some key questions: What are the views of Islamic teachings and the Human Rights Charter on LGBT behavior? How can the human rights and religious doctrine match in solving this LGBT problem? What are the LGBT prevention solutions and solutions that can be done? To answer this question, research is done by studying religious texts be it the Qur'an or hadith, and the text of the Human Rights Charter. Both types of texts are examined in various approaches; theological, historical, philosophical, medical, tafsir, hermeneutical, jurisprudence and psychological. Content analisys method was initially performed on the text of the Qur'an and the hadith. Matan hadith explored by takhrij method and study of hadith text. From this study, it is concluded that LGBT behavior in religious doctrine is strictly prohibited. Likewise the Human Rights Charter can not justify LGBT behavior under the pretext of individual freedom. Because individual freedom is automatically limited by other individual freedoms and legislation. Treatment and prevention solutions can be done to LGBT behaviors. Because psychically, LGBT behavior is a psychiatric disease that can be treated and prevented.